- #1

- 134

- 0

## Homework Statement

The proofs:

show (A')^-1 = (A^-1)'

and

(AB)^-1 = B^-1A^-1

## Homework Equations

## The Attempt at a Solution

for the first one:

(A^-1*A) = I

(A^-1*A)' = I' = I

A'(A^-1)' = I

but im not sure how this proves that a transpose inverse = a inverse transpose...

the second i have the same problem. Not sure how this really proves what it's asking.

http://tutorial.math.lamar.edu/Classes/LinAlg/InverseMatrices_files/eq0041M.gif [Broken]

Last edited by a moderator: